English Language Teaching as a Career in Nepal: Social Motives and Drives - Pandey, Gopal Prasad (Nepal Journal of Multidisciplinary Research, 2021)
Research on teacher motivation has developed and expanded since the beginning of the 21st the century and now there is a considerable increase in literature in the areas of teacher motivation research. A number of research studies have been conducted to gain insights into pre-service and in-service teachers’ reasons for choosing teaching as a career. This study aimed at exploring the social motives and drives that force individuals to opt English language teaching as a career. It also aimed at investigating perceived satisfaction level of the participants. Five teachers of English who have been teaching English at different levels of education in Nepal for twelve years now participated in this study. The narrative inquiry approach was adopted as a research design for this study. Interview was used as a method for data collection. The study revealed that social motives, beliefs and individual desires are integral for choosing English language teaching as a career in Nepal. The love for the subject, the social prestige the English teachers deserved and the passion for teaching are some of the dominant reasons regarding why individuals chose ELT as careers in Nepal. Another frequently highlighted reason for career choice among teachers was a desire to work with children and adolescents. They think that the career as an English teacher also provides them with the opportunity to make a social contribution. So, altruistic motivations are highlighted as one the important reasons for deciding to choose English teacher as a career in Nepal.